2006
DOI: 10.1530/eje.1.02100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rosiglitazone on plasma adiponectin levels and arterial stiffness in subjects with prediabetes or non-diabetic metabolic syndrome

Abstract: Objective: Thiazolidinediones have favorable influences on surrogate markers of atherosclerosis such as adiponectin, and arterial stiffness in diabetic patients. However, it is not well known whether these beneficial effects occur in subjects without diabetes, such as prediabetes or the non-diabetic metabolic syndrome (MetS). The present study was therefore designed to evaluate the effectiveness of the insulin-sensitizing agent rosiglitazone on circulating adipocytokine levels and brachial-ankle pulse wave vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 38 publications
3
34
1
3
Order By: Relevance
“…5). Adiponectin response to RGZ in our study conforms with preclinical (Sharabi et al, 2007) and clinical observations, showing a 2.4-to 2.6-fold increase in both nondiabetic and diabetic patients (Kim et al, 2006;Pfü tzner et al, 2008), suggesting relevant PPAR-␥ stimulation. In addition, the up-regulation of PPAR-␥ mRNA adds further support for RGZ engagement with its target (Sommer and Wolf, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…5). Adiponectin response to RGZ in our study conforms with preclinical (Sharabi et al, 2007) and clinical observations, showing a 2.4-to 2.6-fold increase in both nondiabetic and diabetic patients (Kim et al, 2006;Pfü tzner et al, 2008), suggesting relevant PPAR-␥ stimulation. In addition, the up-regulation of PPAR-␥ mRNA adds further support for RGZ engagement with its target (Sommer and Wolf, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Vehicle [aqueous solution containing 2% Tween 80 (w/v) and 0.5% methylcellulose (w/v)], 3 mg/kg RGZ, or 45 mg/kg RGZ was administered by oral gavage daily for 4 weeks in HF rats, in parallel with vehicle; the 45-mg/kg oral dose of RGZ was administered in studies on ZDF rats. The lower dose of 3 mg/kg RGZ was selected as a clinically relevant dose for efficacy in rats (Yue et al, 2001;Kim et al, 2006;Sharabi et al, 2007;Pfü tzner et al, 2008), and the higher dose of 45 mg/kg represented the supraclinical RGZ exposure aimed to addressed the cardiorenal liability in these models.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, as metabolic syndrome by itself is associated with inflammation, there might be the possibility that resistin is rather associated with inflammation markers that would appear at different stages of metabolic syndrome development, and its correlation with other metabolic and anthropometric parameters like glucose, blood lipids, and BMI is just a secondary effect. Indeed, pharmacological approaches with TZD reduce resistin levels (44,45), although not all reports are consistent with these findings (46).…”
Section: Independent Variablementioning
confidence: 96%
“…In our study, a statistically meaningful distinction wasn't seen in terms of PWV and Alx values between, the patient groups who were divided into groups according to their diet, exercise, oral antidiabetic and insulin treatments. In a study by Kim et al [25] it was shown that rosiglitazone decreases PWV by increasing the insulin sensitivity. In another study it was shown that insulin treatment increases PWV [26] possibly due to increased anabolic effects of insulin.…”
Section: Discussionmentioning
confidence: 98%